Dari Ritual ke Festival: Menenun Identitas Budaya dan Pengembangan Pariwisata Melalui Tradisi Sego Wiwit di Candi Ngawen - Nugraha Nugraha; Siska Nurazizah Lestari; Indra Fibiona (Local History & Heritage, 2025)
Sego Wiwit is a ritualized expression of harvest gratitude within Javanese agrarian communities, embodying an ecological–spiritual worldview rooted in local cosmology and place-based practices. Recent integration of this ritual into the Ngawen Temple Festival marks a significant spatial and functional shift that raises critical questions regarding cultural meaning, community agency, and heritage sustainability. This study examines how the spatial configuration of Ngawen Temple mediates the transformation of Sego Wiwit from a localized agrarian rite into a public cultural festival, and how this transition reshapes its cultural significance and social function. Guided by the concept of living heritage, the research employs a qualitative approach combining ethnographic observation, participatory spatial mapping, and document analysis. The findings reveal that the monumental and sacred character of Ngawen Temple actively reorients Sego Wiwit from a field-based ritual of ecological reciprocity toward a performative medium of collective memory, identity negotiation, and cultural visibility, while retaining core agrarian symbolism. The study argues that heritage sustainability is not achieved solely through the preservation of ritual forms, but through the maintenance of spatial meanings, communal participation, and adaptive interpretation amid ecological, touristic, and urban pressures.